2014
DOI: 10.1073/pnas.1410159111
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of nonspecific interactions in amyloid nucleation

Abstract: Protein oligomers have been implicated as toxic agents in a wide range of amyloid-related diseases. However, it has remained unsolved whether the oligomers are a necessary step in the formation of amyloid fibrils or just a dangerous byproduct. Analogously, it has not been resolved if the amyloid nucleation process is a classical onestep nucleation process or a two-step process involving prenucleation clusters. We use coarse-grained computer simulations to study the effect of nonspecific attractions between pep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 74 publications
8
172
5
Order By: Relevance
“…(There is an additional feature: the re-increase of N * for a low ∆ αβ = −18 k B T at very high concentrations, which we do not fully understand and will not be discussing further). These values of 'critical nucleus' size are within the range obtained by the coarse-grained molecular simulations of Sarić et al 29 : from 2 to 14; they also fall within the experimentally observed values (2 to roughly 25) 80 . Notably, the fact that N * is not a constant value in Fig.…”
Section: The Fastest Growing Nucleisupporting
confidence: 88%
See 2 more Smart Citations
“…(There is an additional feature: the re-increase of N * for a low ∆ αβ = −18 k B T at very high concentrations, which we do not fully understand and will not be discussing further). These values of 'critical nucleus' size are within the range obtained by the coarse-grained molecular simulations of Sarić et al 29 : from 2 to 14; they also fall within the experimentally observed values (2 to roughly 25) 80 . Notably, the fact that N * is not a constant value in Fig.…”
Section: The Fastest Growing Nucleisupporting
confidence: 88%
“…It is suggested that these amorphous micelles serve as intermediates, or initiation states for amyloid nucleation 63 . This generic hypothesis of the role of micelles is indirectly hinted by the increase in β-sheet structural content while losing their original α-helix content 62 , and is further supported by molecular simulation of coarse-grained peptides 29,64 . These facts imply an alternative aggregation pathway for amyloid fibrils: the two-step nucleation mechanism as described in Fig.…”
Section: Two-step Nucleation Mechanism Micellation Of Soluble Peptidesmentioning
confidence: 81%
See 1 more Smart Citation
“…We employ a minimal Monte Carlo computational model that reproduces fibril nucleation, as described in our previous work 45,104 . Briefly, the model accounts for the fact that amyloidogenic peptides and proteins exist in minimally two states: a state in solution (denoted "s") that can form disordered oligomers, and a higher free-energy state that can form the β-sheet enriched fibrils (denoted "β") 104,109 .…”
Section: B Computer Simulations Of Amyloid Nucleationmentioning
confidence: 99%
“…The "s" -"β" interaction was set to sβ = ss + 1kT , as in our previous work 104 . Throughout the text k denotes Boltzmann's constant and T the temperature.…”
Section: B Computer Simulations Of Amyloid Nucleationmentioning
confidence: 99%